Religious Legitimation in Family-Based Terrorism in Indonesia: A 3N Model Analysis of the 2018 Surabaya Bombings - Suratno; Siraj, Fuad Mahbub (KALAM, 2025)
The 2018 Surabaya church bombings marked a turning point in the emergence of family-based terrorism in Indonesia, demonstrating how religious beliefs can be used to legitimize violence involving entire families. This study examines how religious legitimation is constructed within family-based terrorism through narratives, needs, and networks by applying Kruglanski et al.'s 3N Model. Using library research with a qualitative descriptive-narrative approach, this study analyzes the ideological construction underlying the 2018 Surabaya bombings. The findings reveal that religious legitimation is differently constructed among family members. Fathers tend to adopt concrete narratives that explicitly justify violent jihad; mothers internalize more abstract narratives that reinforce ideological commitment, while children receive latent narratives through socialization and obedience. The study also identifies a shift in the interpretation of qitāl jihad from qitāl tamkīn to qitāl nikāyah as the dominant collective narrative. Moreover, fathers are primarily driven by ideological needs, mothers by psychological needs, and children by subordinated needs, all reinforced through pro-ISIS networks such as JAD, JAK, JAT, and MIT. The study concludes that religious legitimation constitutes a key theological mechanism sustaining family-based terrorism and highlights the importance of theological counter-narratives alongside multi-level prevention strategies.